ECOLOGICAL INDICES OF MANGROVE GASTROPODS COMMUNITY IN NICKEL MINING IMPACTED AREA OF POMALAA, SOUTHEAST SULAWESI - Muhammad Purnama; Slamet Budi Prayitno; Max Rudolf Muskananfola; Suryanti Suryanti (SEAMEO BIOTROP, 2024)
Article Highlights- Gastropods (Invertebrates: Mollusca) have the potential to be developed as biological indicators of the health of coastal aquatic environments- The development of gastropod communities has been proven to provide a significant ecological response in assessing environmental quality in the mangrove in relation to overburden waste input from nickel mining activities.- Overburden waste systemically degrades the ground floor (substrate) of the mangrove ecosystem as an area where the entire life cycle of the gastropod community is carried out.AbstractThis research aimed to determine the structure of gastropod community in the nickel mining impact area in the mangrove ecosystem of Tambea Village, Pomalaa District, Southeast Sulawesi Province. The scope of this research was gastropod community influenced by nickel mining activities, especially the impact of overburden waste input (reddish-orange colored sediment) toward the health status of the aquatic environment based on the ecological indices of the gastropod community in the mangrove ecosystem of Tambea Village. Two sampling methods were adopted in this research: (1) purposive sampling method to determine stations (locus) and (2) simple random sampling method to determine the distribution of substations or sampling points. Gastropod samples were taken using handpicking techniques. The structure of gastropod community in mangrove area affected by overburden waste showed low diversity index values (H’ = 0.81), low species richness (R = 1.75), moderate evenness (E = 0.50), and dominance of certain species (C = 0.54). The results of this research showed the massive impact of overburdened waste, which can systemically degrade the life of the typical fauna that make up the mangrove ecosystem. Three gastropods species were observed to live in the research location, namely Telescopium telescopium, Terebralia sulcata, and Terebralia palustris having low abundance (1-9 ind./m2) which can survive in environment exposed to overburden waste. Many of gastropod species were found dead, indicated by the finding of 2 shells of Ellobium aurisjudae. The input of overburdened waste may imply degradation system of the aquatic environment, especially in the mangrove ecosystem. This research offers outlooks of overburden waste on aquatic biota in mangrove ecosystems and other complimentary ecosystems. In the end, the condition of the gastropod community in a watered area becomes a basis of the health status of the water environment.